The effects of pre-planting refrigeration on bulbs over the development and yield of garlic 'Chines', 'Contestado' and 'Quiteria' - Braz, L. T. [UNESP]; Da Silva, E. J. [UNESP]; Castellane, P. D. [UNESP] (My University, 1997)
The objective of this research uas to evaluate the effect of five pre-planting refrigeration periods previously to the cloves planting (0,10,20, 30 and 40 days at a temperature of 4.0 ± 1° C and three garlic cultivars ('Chines', 'Contestado' and 'Quiteria') uere used. According to the obtained results it was observed that the best preplanting refrigeration period was dependent upon the cultivar behavior. For the 'Chines' well adapted to the region, there was no effect of the pre-planting refrigeration period up to 30 days after treatment on the plant height, bulb weight, and total bulb production. 'Contestado' the best pre-planting refrigeration period was 40 days however, there was no statistical difference among 30 and 40, days for the 'Quiteria'. For both cultivars pre-planting refrigeration periods under 20 days, there was no clove's formation.
Keywords: Allium sativum; Cultivars; Preplanting refrigeration; Production; Vernalization